PENINGKATAN KEMAMPUAN MENYIMAK CERITA MELALUI PENERAPAN MODEL PEMBELAJARAN TIM PENDENGAR PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 007 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Gusliarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by the lack of listening skills obtained by the students, it is seen from the results of an assessment of the listening skills of students still achieved an average grade 56.32 or reach under the KKM predetermined value is 70. This study aims to determine whether the Team Learning model Listener can improve listening skills of students in the subject of Indonesian student Class V SD Negeri 007 Pagaran Tapah Darussalam Rokan Hulu. The subjects were 38 students in the academic year 2014-2015. Form of research is classroom action research. The data collection technique used is the technique of test and non test. Based on the results, it can be concluded that the ability to listen to the story class V students of SD Negeri 007 Pagaran Tapah Darussalam Rokan Hulu can be improved by applying the learning model listener team. On average ability to listen to stories of students in the early test is average with the average value of 56.32 by the medium category, and in the first cycle rose to 69.47 in the medium category, while in the second cycle listening skills of students categorized as high with the percentage of the average value of 76, 58 with a high category. Therefore, the success rate has exceeded 70 of the total number of students, which means that most students have achieved success predetermined value (minimum 75%).